(untitled) (Global Journals of Research in Engineering, 2023)
The Entropic and Statistical Method of The Analysis Esma Allows Calculating Losses In Different Refrigeration Plant Components and Comparing them to Define the Elements that Need Measures to Increase their Operation Efficiency The paper presents results of analysis existed refrigeration plants used for retail applications The ESMA was applied to investigate some operating refrigeration plants equipped with monitoring system and define elements for further optimization The initial date for analysis were date taking from monitoring system pressures and temperatures in working points The description of calculation method was given The degree of thermodynamic efficiency was calculated This result could not be achieved using a traditional method of comparison refrigeration systems by using a coefficient of performance COP or seasonal efficiency as an only efficiency criterion The prospect of the ESMA application to analyse operation and optimization of existing refrigerating systems as well as to design new refrigerating systems consists in that it allows refusing expensive equipment for improvement refrigeration plant efficiency